Supplemental effect of different levels of energy and protein along with groundnut straw (Arachis hypogaea L.) based ration on nutrient utilization in dromedary camels - GUPTA, LOKESH; ROY, A K; TIWARI, G S (The Indian Journal of Animal Sciences, 2017)
The present investigation was carried out to study the effect of feeding different levels of energy and protein supplementation along with groundnut haulms (Arachis hypogaea L.) on nutrient utilization in dromedary camels. Three concentrates mixtures were formulated, viz. high protein and low energy (T1); high energy and low protein (T2); and medium protein and energy (T3). The digestibility coefficients for dry matter and organic matter were higher in T3 as compared to T2 and T1 but there was nonsignificant difference between T1 and T2 on one hand, and between T1 and T2 on the other hand. There was nonsignificant difference between the groups for NDF, ADF and hemicellulose digestibility. The digestible crude protein (DCP) content was significantly higher in T1 followed by T3 and T2 but there was reverse trend for total digestible nutrient (TDN) content. The nitrogen balance was significantly lower in group fed on high energy and low protein content through the concentrate mixture. The results of the study concluded that the nutrient utilization was higher in T3 treatment as compared to either high protein or high energy supplementation.